Islamic Education Teachers’ Perceptions of the Curriculum Change from the 2013 Curriculum to the Independent Curriculum - Muhammad Ma'ruf Asy'ari; Riza Arif M.Z; Indah Aminatuz Zuhriyah; Muh. Noaf Afgani (Didaktika: Jurnal Kependidikan, 2024)
Curriculum change is one of the problems that arises related to the curriculum. There were various responses from teachers, students and parents regarding this curriculum change. Some of them argued that the curriculum was changed too quickly, giving rise to statement "change minister, change curriculum". This research uses a qualitative approach to the type of literature study (library research). Library study research is a type of research where data is taken through the process of reviewing books, journal articles, and notes related to the problem to be solved (Sari & Asmendri, 2020, p. 43). In this research, researchers studied several journal articles related to the research themes raised and then analyzed them using research procedures according to Kuhltau (Kuhltau, 2002) Perception in the narrow sense is defined as vision, meaning the way an individual sees something. Meanwhile, in a broad sense, perception is defined as a view or understanding, meaning the way an individual views or understands something (Rezki et al., 2020, p. 32). Kottler in Ririn Agustina and Dea Mustika states that perception is a process through which individuals select, organize and interpret information in order to obtain meaningful ideas (Agustina & Mustika, 2023, p. 362). Changing the curriculum from the 2013 curriculum to the independent curriculum is a good thing planned by the government to improve the quality of education in Indonesia due to the Covid-19 pandemic. So that the results of changing the curriculum can be seen in the field, it must be supported by teachers who are competent in their fields.